2015
DOI: 10.1016/j.jaut.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose interleukin-2 fosters a dose-dependent regulatory T cell tuned milieu in T1D patients

Abstract: Most autoimmune diseases (AID) are linked to an imbalance between autoreactive effector T cells (Teffs) and regulatory T cells (Tregs). While blocking Teffs with immunosuppression has long been the only therapeutic option, activating/expanding Tregs may achieve the same objective without the toxicity of immunosuppression. We showed that low-dose interleukin-2 (ld-IL-2) safely expands/activates Tregs in patients with AID, such HCV-induced vasculitis and Type 1 Diabetes (T1D). Here we analyzed the kinetics and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
174
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(198 citation statements)
references
References 66 publications
9
174
0
2
Order By: Relevance
“…A clinical trial with IL-2 plus rapamycin showed transient worsening in beta cell function [42], likely due to either the relatively higher dose of IL-2 employed and/or the rapamycin, with a dramatic increase in natural killer cells and eosinophils. However, early T1D studies with lower IL-2 doses have shown no acute worsening in b-cell function [66,67], and several studies are underway now to further assess safety and efficacy. In an upcoming phase I trial with autologous ex vivo expanded Tregs followed by low dose IL-2, we will evaluate if low dose IL-2 enhances the survival and function of the infused Tregs in vivo.…”
Section: Combination Therapymentioning
confidence: 99%
“…A clinical trial with IL-2 plus rapamycin showed transient worsening in beta cell function [42], likely due to either the relatively higher dose of IL-2 employed and/or the rapamycin, with a dramatic increase in natural killer cells and eosinophils. However, early T1D studies with lower IL-2 doses have shown no acute worsening in b-cell function [66,67], and several studies are underway now to further assess safety and efficacy. In an upcoming phase I trial with autologous ex vivo expanded Tregs followed by low dose IL-2, we will evaluate if low dose IL-2 enhances the survival and function of the infused Tregs in vivo.…”
Section: Combination Therapymentioning
confidence: 99%
“…They were randomly assigned to placebo or IL-2 (0.33, 1, or 3 MIU/d) for a 5-d course and were followed on days 0, 6, and 15. On these days, blood samples were obtained, and ABCA1 gene expression was analyzed in PBMCs using the SurePrint G3 Human GE v2 8360K Microarray (Agilent Technologies; ID: 039494), according to the manufacturer's protocol, as reported (17). ABCA1 gene expression is the average expression measured by two probes (A_24_P235429, A_33_P3422897).…”
Section: Maldi-tof Analysismentioning
confidence: 99%
“…Dans le diabète de type 1, des études préliminaires d'efficacité ont permis de déterminer, chez les patients, la dose d'IL-2 induisant une augmentation des lymphocytes Treg sans que ne soient affectées les cellules effectrices T ou NK. Elle a de plus permis de montrer une réduction de la composante T spécifique des cellules β du pancréas [31,32]. L'ensemble de ces premières études indique donc l'intérêt des thérapies fondées sur des faibles doses d'IL-2 pour le traitement des maladies auto-immunes et inflammatoires.…”
Section: (➜)unclassified